Transportes e circulação: Fixos, fluxos e dinâmicas econômicas no estado de Mato Grosso do Sul - Brasil - Ana Paula Camilo Pereira (Confins, 2018)
This research project intends to analyze and identify the dynamics of fluidity through fixed in the Brazilian state of Mato Grosso do Sul, its role in the national economy, as well as its relationship with the other countries that are part of the Bioceanic Road, designed from the Brazilian cities of Campo Grande-MS to Porto Murtinho-MS, towards the ports of northern Chile. For this, the objective is to verify the transport systems that have progressively incorporated the technical bases in Mato Grosso do Sul, considering in this perspective the inseparable set of engineering systems (the fixed ones) and systems of flows (materials). Regarding transport modes, it is based on the main modalities enabled in the movement of goods and passengers, based on the historical process of development of these modes and their infrastructures. In terms of flows, the movement of people and merchandise is taken as a way of understanding the spatial organization of the circulation and its adjacent relations, in a context that seeks to understand the results of the public policies of transport infrastructure. In summary, this project aims to systematize the economic dynamics of transport modes, recognizing them as one of the most important aspects of the logic of regional economic development.